EVALUATION OF INTRAOCULAR PRESSURE OUTCOMES AND FAILURE RISK FACTORS IN THE COLLABORATIVE STUDY ON BLEB-RELATED INFECTION AND TREATMENT: A PROSPECTIVE STUDY. - Lakra, Marianus Deepak; Kumari, Sindhu; Chaudhary, Kuldeep; Patel, Pinki (Student's Journal of Health Research Africa, 2024)
Background Trabeculectomy remains the primary surgical intervention for glaucoma management, enhanced by adjunctive therapies like mitomycin C, despite the associated risk of complications such as bleb-related infections. The current study utilizes the CBIITS dataset to assess the impact of trabeculectomy on IOP, evaluate the rate of surgical success, and identify factors influencing surgical outcomes and complications. Methods This prospective study included 30 patients undergoing filtering surgeries at Rajendra Institute of Medical Sciences (RIMS), Ranchi, with follow-up at six-month intervals over three years. Intraocular pressure (IOP) was measured preoperatively and postoperatively using Goldmann application tonometry, and surgical success was defined based on IOP thresholds from the World Glaucoma Association. Statistical analyses included Kaplan-Meier survival analysis and Cox proportional hazards models to evaluate outcomes and associated risk factors. Results The study involved 30 patients with a mean age of 62.8 years and a mean follow-up of 12.3 months. Primary open-angle glaucoma was the most common diagnosis (50%). Multivariate analysis indicated that previous glaucoma surgeries significantly impacted treatment outcomes, with 76.7% of patients having no prior surgeries achieving better results. Postoperative complications were observed in 9 patients (30%), with early complications such as hyphema and choroidal detachment occurring in 6 (20%) and 10 (33.3%) cases, respectively. Conclusion Surgical history and lens status are crucial for the success of trabeculectomy in glaucoma management, emphasizing the importance of monitoring postoperative complications. Recommendation Closure of leaky filtering blebs in patients whose vision is believed to be seriously threatened by a possible infection linked to the bleb is recommended.